The Use of Design Sprint Method in Developing the Excellence Program of Integrated Islamic Elementary School (SDIT) Nur Hidayah Surakarta - Rochmawan, Alfian Eko; Ridha, Achmad Rasyid; Abbas, Ngatmin; Primarni, Amie; Puri, Vesa Yunita (Yayasan Azhar Amanaa Yogyakarta, 2023)
The declining number of registrations at the Integrated Islamic Elementary School (SDIT) Nur Hidayah Surakarta serves as the basis for this research. The purpose of this study is to explore the expectations of parents when enrolling their children at the Integrated Islamic Elementary School (SDIT) Nur Hidayah Surakarta. The research findings will be utilized to formulate the strengths offered to the community. The design sprint method is one of the approaches employed to identify these strengths. By utilizing the design sprint method, this study successfully formulated 8 (eight) strengths and discovered 2 (two) weaknesses in the implementation of the elementary school at the Integrated Islamic Elementary School (SDIT) Nur Hidayah Surakarta. The research adopted a qualitative descriptive approach, and a random sample of parents from the Integrated Islamic Elementary School (SDIT) Nur Hidayah Surakarta was interviewed using non-numerical interview techniques. The formulation of strengths at the Integrated Islamic Elementary School (SDIT) Nur Hidayah Surakarta through the design sprint approach assists the school's administration in formulating the strengths offered to the community.